Crimes against Justice under the Legislation of the States of the European Union - Воробчак, Андрій Романович; Воробчак, А. Р.; Воробчак, Андрей Романович; Vorobchak, Andrii R.; Vorobchuk, Andrey R.; Налуцишин, Віктор Володимирович; Налуцишин, В. В.; Налуцишин, Виктор Владимирович; Nalutsyshyn, Viktor V.; Налуцишин, Володимир Вікторович; Налуцишин, В. В.; Налуцишин, Владимир Викторович; et al. (Lifescience Global, 2020)
The countries of the European Union (EU) are united, but above all, each country is autonomous. EU Member States have different legislation on criminal offences. The EU authorities have already suggested the possibility of creating a single system for regulating legal provisions on criminal offences. Studying and comparing the legal systems and responsibilities for crimes against justice in individual countries will facilitate the analysis of the differences in the legislation of the EU countries. The purpose of this paper is to investigate crimes against justice in accordance with the laws of each individual European country. The paper considers the composition of such crimes, as well as the responsibility to which offenders can be brought in case of such crimes. The study uses the methods of analysis and synthesis, analyses legal provisions. General methods of scientific cognition used in this study include dialectical, historical, the Aristotelian method, method of systematic data analysis, formal legal method, method of legal modelling and comparative legal method. The study investigates the legal framework of European countries, in particular criminal codes and laws. This study systematises and groups the received information and data on criminal liability of judges for unlawful decisions. The European practices in punishing those who do not comply with court rulings and judgments are also analysed. A study of the legal system in individual EU countries will help distinguish between positive and negative aspects in the legislation. In addition, this study allows to consider and analyse the most effective laws, provisions, and principles that can be implemented in the current legal system of different countries of the world.

Країни Європейського Союзу (ЄС) об’єднані, але перш за все кожна країна є автономною. Держави-члени ЄС мають різне законодавство щодо кримінальних правопорушень. Влада ЄС вже пропонувала можливість створення єдиної системи регулювання законодавчих положень про кримінальні правопорушення. Вивчення та порівняння правових систем та відповідальності за злочини проти правосуддя в окремих країнах полегшить аналіз відмінностей у законодавстві країн ЄС. Метою даної роботи є розслідування злочинів проти правосуддя відповідно до законодавства кожної окремої європейської країни. У статті розглядається склад таких злочинів, а також відповідальність, до якої можуть бути притягнуті правопорушники у разі вчинення таких злочинів. Дослідження використовує методи аналізу та синтезу, аналізує законодавчі положення. Загальні методи наукового пізнання, що використовуються в цьому дослідженні, включають діалектичний, історичний, аристотелевський метод, метод систематичного аналізу даних, формально-правовий метод, метод юридичного моделювання та порівняльно-правовий метод. Досліджується правова база європейських країн, зокрема кримінальні кодекси та закони. Це дослідження систематизує та групує отриману інформацію та дані про кримінальну відповідальність суддів за незаконні рішення. Також аналізується європейська практика покарання тих, хто не виконує судових рішень та постанов. Дослідження правової системи в окремих країнах ЄС допоможе розрізнити позитивні та негативні аспекти законодавства. Крім того, це дослідження дозволяє розглянути та проаналізувати найефективніші закони, положення та принципи, які можуть бути впроваджені в сучасні правові системи різних країн світу.

Страны Европейского Союза (ЕС) объединены, но, прежде всего, каждая страна автономна. Государства-члены ЕС имеют разное законодательство об уголовных преступлениях. Власти ЕС уже предложили возможность создания единой системы регулирования положений законодательства об уголовных преступлениях. Изучение и сравнение правовых систем и ответственности за преступления против правосудия в отдельных странах облегчит анализ различий в законодательстве стран ЕС. Целью данной статьи является расследование преступлений против правосудия в соответствии с законодательством каждой отдельной европейской страны. В статье рассматривается состав таких преступлений, а также ответственность, к которой могут быть привлечены правонарушители в случае совершения таких преступлений. В исследовании используются методы анализа и синтеза, анализируются положения законодательства. Общие методы научного познания, используемые в этом исследовании, включают диалектический, исторический, аристотелевский метод, метод систематического анализа данных, формально-правовой метод, метод правового моделирования и сравнительно-правовой метод. Исследуется правовая база европейских стран, в частности уголовные кодексы и законы. В данном исследовании систематизированы и сгруппированы полученная информация и данные об уголовной ответственности судей за неправомерные решения. Также анализируется европейская практика наказания тех, кто не подчиняется постановлениям и решениям судов. Изучение правовой системы в отдельных странах ЕС поможет различить положительные и отрицательные аспекты законодательства. Кроме того, данное исследование позволяет рассматривать и анализировать наиболее эффективные законы, положения и принципы, которые могут быть реализованы в действующей правовой системе разных стран мира.
Vorobchak A. R. Crimes against Justice under the Legislation of the States of the European Union / A. R. Vorobchak, V. V. Nalutsyshyn, V. V. Nalutsyshyn, O. V. Popovych // International Journal of Criminology and Sociology. – V. 9. – Lifescience Global, 2020. – P. 1526-1532.
Keywords: crime; justice system; European Union; legislation; Criminal Code; злочин; система правосуддя; Європейський Союз; законодавство; Кримінальний кодекс; преступление; система правосудия; Европейский Союз; законодательство; Уголовный кодекс; Research Subject Categories::LAW/JURISPRUDENCE